Detection and analysis of Brain Tumor from MRI by Fully Convolutional Neural Network method - et.al, T. Sandhya Rani (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Although it seems that the technology used in MRI is technologically advanced, we now use MRI to detect tumors based on human skills and knowledge. Although this method is proven to be accurate in most cases, sometimes the human eye does not work until it detects a slight deviation. In countries like India, there are no oncologists or neurologists. According to a report from 2018, the country is facing a shortage of health workers, with only 2,000 cancer specialists treating 10 million patients in rural areas, where the number of cancer specialists is very low, and its condition worse.